International Cooperation to Combat Money Laundering in the Southeast Asia: A Narrative Perspective in Vietnam - Tran, Huyen Quang (2020)
The fight against money laundering is a special concern of international, regional, and national scale. In recent years, Vietnam is a country that is significantly affected by this type of crime. To combat money laundering need not only to strengthen domestic legislation’s system and professional task forces, but also to enhance international cooperation among multilateral and bilateral agreements between host countries and their counterparts. Using the document analysis combined with legal norm’s analysis, this paper draws the nature of money laundering in Vietnam and also analysis Vietnam’s perspectives to implement their national efforts to curb this crime. The research highlights the significant role of international cooperation in this battle rather than building national improvements. Some recommendations to improve the effectiveness of international cooperation to fight money laundering in general as well as to enhance policing plans of Vietnam’s law enforcement agencies that call for special attentions in the end of the research.Keywords: Money laundering, money laundering prevention, international cooperation, VietnamDOI: 10.7176/JLPG/96-09Publication date: April 30th 202